1994
DOI: 10.1002/cber.19941270108
|View full text |Cite
|
Sign up to set email alerts
|

Chlorotrioxorhenium. Neue Synthesen, Reaktionen und Derivate

Abstract: lb-e) are generated from R e 2 0 t and either ZnX2, (noxides in good yields. These synthetic routes have the advan-C4H9)3SnX, [(n-C,H&N]X, or [ (CAHS)4P]X in clean reactions. tage to proceed under very mild conditions. The adducts of Compounds la-f form with stable six-coordinate adducts 2,2'-bipyridine with halorhenium(VI1) oxides show characte-XRe03.L (2a-f, 3a, 4a, 5a: L = N,N'-ligand) upon addition ristic thermogravimetric (TG) behavior that reflects the volaof the free ligand L, e.g. 2,2'-bipyridine. l a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…All compounds were purchased from Aldrich unless stated otherwise. The ligand p ‐tolyl‐DAB,20 compounds 1 – 3 ,13 4 ,21 5 ,22 7 − 9 ,23 10 ,13 [ReOCl 3 (PPh 3 ) 2], 24 [ReOCl 3 (dppe)],25 13, 26 14, 27 15, 25 16, 28 17, 25 18, 27 and 19 27 were synthesized according to published procedures. Complexes 13 – 19 were a kind offer from Dr. Isabel Santos and Dr. António Paulo from the Instituto de Tecnologia Nuclear, Sacavém, Portugal.…”
Section: Methodsmentioning
confidence: 99%
“…All compounds were purchased from Aldrich unless stated otherwise. The ligand p ‐tolyl‐DAB,20 compounds 1 – 3 ,13 4 ,21 5 ,22 7 − 9 ,23 10 ,13 [ReOCl 3 (PPh 3 ) 2], 24 [ReOCl 3 (dppe)],25 13, 26 14, 27 15, 25 16, 28 17, 25 18, 27 and 19 27 were synthesized according to published procedures. Complexes 13 – 19 were a kind offer from Dr. Isabel Santos and Dr. António Paulo from the Instituto de Tecnologia Nuclear, Sacavém, Portugal.…”
Section: Methodsmentioning
confidence: 99%
“…Both compounds are easily and quantitatively available from Re 2 O 7 and can be used in situ for the reaction with the organylating reagents without rhenium loss (eqs 4 and 5). 9,10 Covalent perrhenates such as Me 3 SiOReO 3 and Me 3 SnOReO 3 are also suitable precursor compounds of R-ReO 3 complexes. 11 It has been shown that organozinc precursors are useful for the preparation of long-chain alkylrhenium oxides (2-14) 12 and σ-arylrhenium oxides (25-33) 13 while methyl-(1), alkenyl-(15-18, 22-24), and alkynyl-(19-21) rhenium(VII) oxides and nonperalkylated cyclopentadienylrhenium(VII) oxides (35,36) are available with organotin precursors.…”
Section: Introductionmentioning
confidence: 99%
“…After removal of the solvent, pure MTO can easily be obtained by recrystallization or sublimation. The employed rhenium precursors gave generally good yields ranging from 66–92 % and are, by far, superior to dirhenium heptoxide ( 5 ), chloro trioxorhenium22 ( 6 ) or trimethylsilyl perrhenate23 ( 7 ) as more reactive rhenium sources (Table 2). The best results were obtained with acetic and isobutyric acid derivatives.…”
Section: Resultsmentioning
confidence: 98%